Learning English Vocabulary with Taboo Game: A Case Study of Indonesian Junior High School Students - Siregar, Mega Agnesya; Fithriani, Rahmah (Universitas Cokroaminoto Palopo, 2023)
Vocabulary serves as the basis for the four language skills. However, for many EFL learners, vocabulary mastery is difficult to achieve. This situation requires English teachers to find and utilize different approaches to help make vocabulary learning more enjoyable yet engaging for their students. This study aimed to elucidate English as a foreign language (EFL) learners' reflections after utilizing the Taboo game for vocabulary learning and to explore their perceptions of its benefits. A qualitative method was used in the current study. The data were gathered through in-depth interviews and questionnaires. This research was carried out at one private junior high school in Medan, Indonesia. Thirty-four second-year students agreed to participate in the study (15 females; 19 males). The results of data analysis through frequency count and Content Analysis revealed that most students were satisfied with learning vocabulary through the Taboo game. Furthermore, in terms of their perceptions, the students reported three benefits (1) Improvement of vocabulary mastery, (2) Enhanced vocabulary recall (3) Higher engagement. In general, the Taboo game was perceived positively by all the student participants. Moreover, the Taboo game assists in learning and understanding materials, making it easier to know and learn new vocabulary and increasing their learning creativity.